Pendampingan Penguatan Administrasi dan Dokumen Mutu dalam Rangka Akreditasi SMPIT Ar-Rasyidiyah Kecamatan Batang Tuaka, Kabupaten Indragiri Hilir, Provinsi Riau - Fahrina Yustiasari Liriwati; Zulhimma Zulhimma; Zulhammi, Zulhammi; Ali Pirdaus (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
This Community Service Program (PKM) was carried out to improve the accreditation readiness of SMPIT Ar-Rasyidiyah, Batang Tuaka Subdistrict, Indragiri Hilir Regency, Riau Province, through strengthening school administration and preparing quality documents in accordance with the 2020 Educational Unit Accreditation Instrument (IASP) that will be fully implemented in 2025. The main problems faced by the school included incomplete administrative evidence, limited understanding of the accreditation team regarding the latest technical guidelines, and suboptimal management of digital documentation to support the accreditation process. To address these challenges, the program was implemented through several stages: needs analysis, dissemination of accreditation guidelines, training in the preparation of quality documents, technical assistance in organizing physical and digital files, and evaluation of outcomes. The results showed a significant improvement in the completeness of quality documents, increasing from 62% to 91%. Moreover, the competence of the accreditation team in understanding the IASP 2020 indicators improved, as reflected in their enhanced ability to interpret instruments and prepare supporting evidence. Another innovation was the establishment of a digital storage system using Google Drive, which facilitated integrated access and management of documents. Overall, this mentoring program contributed substantially to improving school management quality and can serve as a replicable model for other Integrated Islamic schools in Indragiri Hilir Regency and surrounding areas.